Olsalazine in active ulcerative colitis. - Selby, W; Barr, G; Ireland, A; Mason, C; Jewell, D (1985)
Olsalazine (azodisalicylate) is a new drug in which two molecules of 5-aminosalicylic acid are linked by an azo bond. Its role in the treatment of mildly active, distal ulcerative colitis was investigated. Sixty patients were randomly allocated to receive olsalazine 1 g or a placebo as a retention enema nightly for two weeks. Clinical improvement was seen in 19 (66%) and sigmoidoscopic improvement in 17 (59%) of the 29 patients receiving olsalazine compared with 12 (43%) and 11 (39%), respectively, of the 28 in the control group. These differences were not significant. In a second trial 40 patients were randomised to receive oral olsalazine 2 g daily or a placebo capsule for two weeks. Significant clinical and sigmoidoscopic improvement was seen in the patients receiving oral olsalazine compared with the patients receiving placebo capsules. Oral olsalazine may be valuable in the treatment of mildly active ulcerative colitis. Its role in maintaining remission is yet to be determined.